2001
DOI: 10.1074/jbc.m009180200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anoxia and the Mitochondrion on Expression of Aerobic Nuclear COX Genes in Yeast

Abstract: Eucaryotic cells contain at least two general classes of oxygen-regulated nuclear genes: aerobic genes and hypoxic genes. Hypoxic genes are induced upon exposure to anoxia while aerobic genes are down-regulated. Recently, it has been reported that induction of some hypoxic nuclear genes in mammals and yeast requires mitochondrial respiration and that cytochrome-c oxidase functions as an oxygen sensor during this process. In this study, we have examined the role of the mitochondrion and cytochrome-c oxidase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Insofar as oxygen is the electron acceptor for this process, it was surprising that gene expression studies with yeast revealed that most COX genes are expressed, albeit at low levels, under anoxic conditions (31,65). Moreover, the promitochondria from anoxic yeast cells retain significant levels of the polypeptide subunits of Cco (66) and the ability to respire (67). These findings suggested a physiological role for Cco in the absence of O 2 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Insofar as oxygen is the electron acceptor for this process, it was surprising that gene expression studies with yeast revealed that most COX genes are expressed, albeit at low levels, under anoxic conditions (31,65). Moreover, the promitochondria from anoxic yeast cells retain significant levels of the polypeptide subunits of Cco (66) and the ability to respire (67). These findings suggested a physiological role for Cco in the absence of O 2 .…”
Section: Discussionmentioning
confidence: 63%
“…Yeast cells were grown in SSG-TEA, a semisynthetic medium (66), supplemented with Tween 80, ergosterol, silicon antifoam, and amino acids and uracil, as needed (14). Aerobic cultures and precultures were grown in a controlled environment incubator shaker (New Brunswick Scientific) at 200 rpm and 28°C and harvested in midlogarithmic growth phase.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced mitochondrial structures have been observed in both dried seeds and in meristematic zones in a variety of plants (41)(42)(43). Anaerobiosis is another scenario where such protomitochondria have been proposed to exist in both plants and yeast (2,6,12,19,23). Plant studies, like those in many animals, have been hampered by the lack of extended anoxia tolerance of cells to truly observe mitochondria that have been formed in the absence of oxygen.…”
Section: Bn-polyacrylamide Gels Of Electron Transport Chainmentioning
confidence: 99%
“…Such studies have shown that mammalian mitochondria may function as oxygen sensors and secondary messengers by increasing their generation of reactive oxygen species during the early stages of oxygen deprivation (5). Induction of some "hypoxic nuclear genes" in both mammals and yeast requires mitochondrial respiration and cytochrome c oxidase has been shown to function as a key oxygen sensor during this process (6).…”
mentioning
confidence: 99%
“…Our results pointed to an exciting possibility of using CcO activity modulators for controlling myocardial injury associated with ischemia and oxidative stress conditions. Cytochrome c oxidase (CcO) 3 is the terminal oxidase of the mitochondrial electron transport chain, whose activity is modulated in response to O 2 tension and the work load of the tissue (1)(2)(3)(4)(5)(6). This rate-limiting enzyme is an important site of regulation of mitochondrial respiration and oxidative phosphorylation (7).…”
mentioning
confidence: 99%